Analysis of squalene and its transformation by-products in latent fingermarks by ultrahigh-performance liquid chromatography-high resolution accurate mass Orbitrap™ mass spectrometry - Dorakumbura, Buddhika; Busetti, F.; Lewis, Simon (2019)
Transformation of squalene and its by-products in latent fingermarks over time under different storage conditions (light, dark, and underwater) was examined through ultrahigh-performance liquid chromatography-high resolution accurate mass Orbitrap™ mass spectrometry. Complications of assessing fingermark compositional variation over time using multiple samples with varying initial compositions were elucidated and a more rational approach was successfully demonstrated. Squalene was detected in all fresh natural fingermarks deposited on non-porous surfaces and the amount ranged between 0.20 to 11.32 μg/5 fingertips. A notable difference in the transformation of squalene was observed with different storage conditions, where a dark aquatic environment accelerated degradation of squalene compared to dark but dry conditions. Squalene monohydroperoxide was extremely short-lived in natural deposits while the amount of squalene epoxide was still increasing relative to the initial amount, after ageing under dark and aquatic conditions for up to 7 days. Some oxidation by-products of cholesterol were also tentatively identified, which exhibited a growth over time against their initial concentration under any of the storage condition tested. These by-products, therefore, show potential as biomarkers for targeted visualisation of aged deposits.